On the fragility of fractional-order PID controllers for FOPDT processes - Padula, Fabrizio; Visioli, A. (Elsevier Inc, 2016)
© 2015 ISA. Published by Elsevier Ltd. All rights reserved.This paper analyzes the fragility issue of fractional-order proportional-integral-derivative controllers applied to integer first-order plus-dead-time processes. In particular, the effects of the variations of the controller parameters on the achieved control system robustness and performance are investigated. Results show that this kind of controllers is more fragile with respect to the standard proportional-integral-derivative controllers and therefore a significant attention should be paid by the user in their tuning.